Cultural Ecosystem Services and Farmer’s Willingness to Pay. A case study in Agricultural Communities in South Tapanuli - Harahao, Hamid Arrum; Yonariza; Endrizal Ridwan; Yuerlita (Agrotekma: Jurnal Agroteknologi dan Ilmu Pertanian, 2023)
The study focuses on valuing Cultural Ecosystem Services (CES) in the Sibual-buali area of South Tapanuli, North Sumatera, Indonesia, and its implications for agricultural development and conservation. The research aims to characterize CES and determine their economic value by assessing farmers' willingness to pay (WTP). Using a descriptive and quantitative research design, a household survey with 71 respondents was conducted using the contingent valuation method (CVM). The study reveals the cultural heritage values and community involvement in conserving CES, demonstrating a deep understanding of the forest's protection and the interconnectedness between the forest, agriculture, and community well-being. The findings emphasize the importance of local wisdom, traditional knowledge, and community engagement in agriculture and CES preservation. Additionally, the study identifies education and income as influential factors in respondents' WTP for CES, indicating their positive impact on environmental valuation and conservation efforts. Gender, marriage status, and age were found to have no significant influence on WTP. These findings contribute to comprehending the economic significance of CES and its relationship to sustainable agricultural practices.